KEBUTUHAN INFORMASI GURU DI ERA DIGITAL: STUDI KASUS DI SEKOLAH DASAR LABSCHOOL UNIVERSITAS PENDIDIKAN INDONESIA - Silvana, Hana; Rullyana, Gema; Hadiapurwa, Angga (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2019)
This research was conducted with the aim to find out what information is needed by the teacher in supporting teaching and learning activities, to find out the use of Internet-based information sources, and to find out the obstacles that arise in searching information what is done to overcome obstacles in conducting information searches. The method used in this study is a descriptive method. The Informant in this study were teachers of SD Laboratorium School, Indonesia University of Education. The results of the study found that the information needs of teachers were four aspects. Aspects of learning planning, information needs include RPP planning, teacher learning objectives, competencies, indicators, and material scope. Content or material aspects or learning experiences of information needs include student characteristics, forms of learning activities, learning strategies, and learning outcome evaluation tools. The aspects of choosing learning strategies and methods of information needs include learning objectives, students' initial knowledge, student characteristics, time allocation, supporting facilities, and the surrounding situation. The aspect of media selection, information needs include learning objectives, material scope, student characteristics, supporting features and technological development. Obstacles in information retrieval include time, ICT skills, weak and lazy search techniques.